Réponses

Meilleure réponse !
2014-04-24T19:54:00+02:00
A = -2 + x(-5x + 7)
A = -2 - 5x² + 7x
A = -5x² + 7x - 2

B = (x-1)(-5x + 2)
B = -5x² + 2x + 5x - 2
B = -5x² + 7x - 2

C = x(-5x + 5) + 2(x-1)
C = -5x² + 5x + 2x - 2
C = -5x² + 7x - 2

D = -5x(x-2) - (3x + 2)
D = -5x² + 10x - 3x - 2 
D = -5x² + 7x - 2 



A =  \frac{3}{8} -  \frac{5}{2} +  \frac{1}{6}\\  A =  \frac{18}{48} -  \frac{120}{48} +  \frac{8}{48}\\   A =  \frac{-94}{48} =  \frac{-47}{24}



B =  \frac{5}{3} + 1 -  \frac{1}{2}
\\B =  \frac{10}{} +  \frac{6}{6} -  \frac{3}{6}
\\B =  \frac{13}{6}


C =  \frac{6}{7} + ( \frac{3}{7})( \frac{1}{2})
\\C =  \frac{6}{7} +  \frac{3}{14}
\\C =  \frac{12}{14} +  \frac{3}{14}
\\C =  \frac{15}{14}



D =  \frac{4}{3} +  \frac{1}{5} +  \frac{4}{5}
\\ D =  \frac{4}{3} + 1
\\D =  \frac{4}{3} +  \frac{3}{3}
\\D =  \frac{7}{3}


mrc mais ducoup j'ai reussi mais mrc quand meme